ANALISIS PENGARUH EKSPOR MIGAS, PMDN, PDB TERHADAP TINGKAT KEMISKINAN DI INDONESIA - Awwalina Alfi Ainurrahmi, ‘Asy'fa; Tutik, Tutik (Penerbit Lafadz Jaya, 2025)
This study analyzes the effect of oil and gas exports, Domestic Investment (PMDN), and Gross Domestic Product (GDP) on poverty levels in Indonesia during the period 1998–2023 using the Error Correction Model (ECM) approach. The objective is to examine both the short-term and long-term relationships between these macroeconomic variables and their impact on poverty reduction. The results show that all three variables have a negative and significant effect on poverty levels. Oil and gas exports reduce poverty by 0.11% in the short term and 0.19% in the long term. PMDN contributes to a 0.06% decrease in poverty in the short term and 0.10% in the long term. Meanwhile, GDP helps reduce poverty by 0.11% in the short term and 0.17% in the long term. The adjusted R² value of 97.21% indicates that the model explains the variation in poverty levels very well. These findings affirm that increasing oil and gas exports, domestic investment, and economic growth are effective strategies for poverty alleviation. Therefore, the government should strengthen and sustain economic policies supporting these three sectors to ensure equitable and sustainable poverty reduction.